Governance and Regulation: Do UK Messages Have International Relevance? - Middlehurst, Robin (International Higher Education, 2015)
Reviews of governance and regulation have occupied three of the four countries of the UK in 2011-2014. The debates, arguments and negotiations that underpin these reviews reveal different ideological positions about the role of the state, balances between accountability and autonomy and democratic participation in the governance of institutions by staff and students. External drivers are also part of the picture as governments and institutions alike seek to position themselves in a changing international context. It is hoped that both the ideological debates and the operational solutions developed in the UK will have wider resonance for other countries and regions engaged in the modernisation, expansion, development or re-construction of their higher education systems.